FEATURES OF THE CONSIDERATION OF INDIVIDUAL LABOR DISPUTES IN THE EAEU COUNTRIES - Z.B. Zhukova,; O.V. Miroshnikova,; M.N. Myrzakhanova, (Academic Journal of Physical and Chemical Sciences, 2019)
The Eurasian integration project was originally based on the idea of creating a single economic space. The issue of political integration in the framework of the EAEU, including the creation of a Eurasian parliament, was discussed in preparation for the launch of the Eurasian integration project. During this period, the Kazakh political institution sought to maximize the number of participants in the Union. Political integration was seen as a way to strengthen Eurasian integration. The creation of the EAEU allowed the free movement of labor across the territories of five member states, which increased the need for harmonized working conditions, and therefore, the issue of harmonization of labor law became relevant for five states. In particular, the resolution of labor disputes, the main elements of which consider the institution of labor law, including the definition and classification of disputes in the EAEU member states. According to the authors, the legal regulation of labor disputes in all member states is based on Soviet legal traditions, that is, similar legal models and concepts.